Penerapan Audit Kepatuhan Atas Prosedur Penjualan Kredit Guna Meningkatan Pengendalian Intern Pada PT Pamolite Adhesive Industry (PAI) Probolinggo - Seger Priantono (Fakultas Ekonomi Universitas Panca Marga, 2015)
The aim of this research is to determine the result and applied of complaint audit on the selling procedure of PT Pamolite Adhesive Industry(PAI) in Probolinggo. The method used in this research is action research which to know the improvement of the intern pressured. The process of compalint audit is done for the unsures of the intern pressured in audit selling procedure which consist of separeted of the functions and the divided the responsibilities, the system of job utilities and the authority of doing practice well in every organizations. The aim of compalint audit is to convince the audit selling procedure is fulled the unsures of intern pressured. The finding of this research is expected that the audit selling procedure is fulled in the intern pressured. For the further researches, the researcher suggests for doing the selling transaction and job divisions of responsibilities well in every parts of selling system. Keywords:complaint audit, selling procedure, intern pressured.